Revisiting Quasicrystals for the Synthesis of 2D Metals - Yadav T.P.; Kumbhakar P.; Mukhopadhyay N.K.; Galvao D.S.; Ajayan P.M.; Ranganathan S.; Chattopadhyay K.; SekharTiwary C. (My University, 2025)
Quasicrystals (QCs) are intermetallic materials with long-range ordering but with lack of periodicity. They have attracted much interest due to their interesting structural complexity, unusual physical properties, and varied potential applications. The last four decades of research have demonstrated the existence of different forms of QC composed of several metallic and non-metallic systems, which have already been exploited in several applications. Recently, with the experimental realization of 2D (atomically thin) metals, the potential applications of these structures have significantly increased (such as inflexible electronics, optoelectronics, electrocatalysis, strain sensors, nano-generators, innovative nano-electromechanical systems, and biomedical applications). As a result, high-quality 2D metals and alloys with engineered and tunable properties are in great demand. This review summarizes the recent advances in the synthesis of 2D single and few layered metals and alloys using quasicrystals. These structures present a large number of active sites for hydrogen evolution process catalysis and other functional properties. In this review, we also highlighted the possibility of using QC to synthesize other 2D metals and to explore their physical and chemical properties. © 2022, The Indian Institute of Metals - IIM.